6-Hydroxyindole is an endogenous long-lasting OATP1B1 inhibitor elevated in renal failure patients. Issue 6 (December 2020) - Masuo, Yusuke; Fujita, Ken-ichi; Mishiro, Kenji; Seba, Natsumi; Kogi, Tatsuya; Okumura, Hidenori; Matsumoto, Natsumi; Kunishima, Munetaka; Kato, Yukio
Abstract: The hepatic uptake transporter organic anion transporting polypeptide (OATP) 1B1 is inhibited by some uremic toxins; however, direct inhibition can only partially explain the delayed systemic elimination of substrate drugs in renal failure patients. This study aimed to examine the long-lasting inhibition of OATP1B1 by uremic toxins and their metabolites. Preincubation of HEK293/OATP1B1 cells with 21 uremic toxins resulted in almost no change in the uptake of a typical substrate [ 3 H]estrone-3-sulfate (E1 S), although some directly inhibited [ 3 H]E1 S uptake. In contrast, preincubation with an indole metabolite, 6-hydroxyindole, reduced [ 3 H]E1 S uptake, even after the inhibitor was washed out before [ 3 H]E1 S incubation. Such long-lasting inhibition by 6-hydroxyindole was time-dependent and recovered after a 3-h incubation without 6-hydroxyindole. Preincubation with 6-hydroxyindole increased the Km for [ 3 H]E1 S uptake with minimal change in Vmax. This was compatible with no change in the cell-surface expression of OATP1B1, as assessed by a biotinylation assay. Preincubation with 6-hydroxyindole reduced [ 3 H]E1 S uptake in human hepatocytes without changes in OATP1B1 mRNA. Plasma concentration of 6-hydroxyindole in renal failure patients increased as renal function decreased, but might be insufficient to exhibit potent OATP1B1 inhibition. In conclusion, 6-hydroxyindole is an endogenous long-lasting OATP1B1 inhibitor with elevated plasma concentrations in renal failure patients. Graphical abstract: Image 1